PLACER DEPOSITS OF DIAMONDS AND THEIR FORMATION CONDITIONS - Підвисоцький, В.Т.; Остафійчук, Н.М.; Башинський, С.І. (Institute of Geological Sciences, NAS of Ukraine, 2023)
This article reviews information from published papers and studies by the authors about placer diamond deposits. Original data were obtained in result of field and laboratory-analytical work carried out in various countries of Africa and South America. The main types of placer diamond deposits – fluvial, fluvioglacial, eolian, and man-made – have been considered and characterized. The main attention is given to fluvial continental placers, which are the most diverse, well-studied and have the greatest industrial importance. Primary, secondary and mixed deposits are distinguished according to the method of feeding; short, moderate and long transport deposits – according to the distance of the diamond-bearing material movement. It is noted that although the short transport placers (deluvial-proluvial and beds of short watercourses) have not industrial value, they are very informative for the searching for root sources. It is important to reliably diagnose these deposits by lithological-facies and mineralogical features during prospecting works. The concepts about the conditions for the formation of diamond placers in various landscape and geological conditions are developed and clarified. Alluvial-proluvial-lacustrine and proluvial-lacustrine types of placers studied in Yakutia and Brazil are characterized in detail. Their characteristic feature is that their productive strata, being re-deposited products of crustal weathering, themselves underwent a hypergenic change at the place of occurrence, which significantly masks the primary conditions of formation. Continental alluvial redeposition and long transport placers, as well as marine, yield the most high-quality expensive diamonds, the average value of which can reach $300–400 per carat. Often, such placers are formed due to the erosion of ancient Proterozoic placers, which belong to the category of fossils. The article summarizes the genetic and morphological types of diamond placers in the form of a principle diagram of the distribution of sedimentary reservoirs of kimberlite minerals. The landscape-dynamic zones of sedimentation are highlighted. A classification scheme of sedimentary reservoirs containing diamond placers has been developed. Continental, transitional and marine environments are distinguished, with further detalization of sedimentation environments – peneplain, alluvial-lacustrine accumulative plain, alluvial-deltaic plain and shelf zones of sea basins. It is shown that the formation of valley placers, their internal structure, thickness, granulometric composition and diamond content of alluvium are influenced by the dynamic phases of the formation of annual valleys. Visualization of the mutual relationship of different morpho-genetic types of placer diamond deposits is given.